2013
DOI: 10.1242/jcs.137703
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved quantitative proteomics implicates the core snRNP protein, SmB, together with the Survival of Motor Neuron protein, in neural trafficking

Abstract: The biogenesis of splicing snRNPs (small nuclear ribonucleoproteins) is a complex process, beginning and ending in the nucleus of the cell but including key stages that take place in the cytoplasm. In particular, the SMN (survival motor neuron) protein complex is required for addition of the core Sm proteins to the snRNP. Insufficiency of SMN results in the inherited neurodegenerative condition, spinal muscular atrophy (SMA). Details of the physical organization of the cytoplasmic stages of snRNP biogenesis ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…The contributions of each of these individual processes remain to be fully evaluated, however the dysregulation of all of these processes taken together likely explains the unique onset and presentation of the disease. For mRNP localization in particular, it remains to be seen how this manifests in vivo , and if local translation defects reported upon SMN deficiency (Fallini et al, 2016) stem from reductions in RNA delivery or from a direct role for SMN in axonal protein synthesis itself (Dombert et al, 2014; Kye et al, 2014; Prescott et al, 2014; Rage et al, 2013; Zhang et al, 2006). The observed defect in mRNP assembly in the cell body occurs upstream of the previously characterized localization defects, which then result in decreased local translation.…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of each of these individual processes remain to be fully evaluated, however the dysregulation of all of these processes taken together likely explains the unique onset and presentation of the disease. For mRNP localization in particular, it remains to be seen how this manifests in vivo , and if local translation defects reported upon SMN deficiency (Fallini et al, 2016) stem from reductions in RNA delivery or from a direct role for SMN in axonal protein synthesis itself (Dombert et al, 2014; Kye et al, 2014; Prescott et al, 2014; Rage et al, 2013; Zhang et al, 2006). The observed defect in mRNP assembly in the cell body occurs upstream of the previously characterized localization defects, which then result in decreased local translation.…”
Section: Discussionmentioning
confidence: 99%
“…Further optimization of cell seeding densities or complexation parameters for different cell systems may provide a way to reduce these negative effects on cell viability [ 45 , 46 ]. Viromer technology has been further developed to suit the needs of different biomolecules (plasmid DNA, siRNA) and has been investigated previously on both neuronal (SHSY5Y) and nonneuronal cell lines (Ramos, RAW264.7 macrophages) [ 47 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that SNRPB may play an essential role in cell division and DNA replication. Interestingly, a previous study showed that SNRPB interacted with dynein cytoplasmic 1 heavy chain 1 (DYNC1H1) (Prescott et al, 2014), a subunit of human cytoplasmic dynein complex that functions in intracellular transport of DNA damage proteins and mitotic spindle positioning in colorectal cancer (Sucularli and Arslantas, 2017). GESA data suggest SNRPB's participation in cell cycle regulation which is largely mediated by the tumor suppressor p53.…”
Section: Discussionmentioning
confidence: 99%